Heterogeneous Expression of Chondroitin Sulfate Glycosaminoglycans and Versican Proteoglycan during Early Development of Rathke's Pouch. (14th December 2014) - Iyengar, Sheelah; Capehart, Anthony A.
Abstract : While much is known regarding morphogenetic factors involved in specification and differentiation of Rathke's pouch, less attention has been given to extracellular matrix (ECM) interactions involved in its formation. The present research investigated localization of two different chondroitin sulfate glycosaminoglycans (CS-GAGs), TC2 and d1C4, and versican CS-proteoglycan (PG) to identify additional ECM molecules involved in formation of the pituitary rudiment. Immunohistochemical evaluation of anterior pituitary primordia between HH15 and HH28 showed these ECM molecules prevalent in basement membrane and surrounding ECM underlying Rathke's epithelia and to a lesser extent between pouch epithelial cells. TC2/d1C4 CS-GAGs and versican showed changing and heterogeneous localization during pouch development that suggested specific roles in cell-ECM interaction during pituitary morphogenesis. TC2 antigen colocalized with versican at early stages in an asymmetric pattern, with particularly strong staining between ventral diencephalon and roof of Rathke's pouch while d1C4 CS-GAG encompassed the entire pouch by HH22 indicating association with a different CSPG. The heparan sulfate proteoglycan, perlecan, used to verify basement membrane structure, was a consistent component of Rathke's pouch. Data show a dynamic and heterogeneous pattern of CS-GAG and versican expression during early chick Rathke's pouch development that suggests new possibilities for ECM function in its establishment and growth.